Strengthening the Literacy and Numeracy of “Kampus Mengajar 4” Program in the Education Unit Medan Belawan State Elementary School - Khairani, Ade Irma; Nofianna, Siti Asnida (Global Education Journal, 2023)
Kampus Mengajar is one of the Ministry of Research, Technology, and Higher Education programs (Merdeka Belajar Kampus Merdeka), which provides a platform for students to be independent in determining their future by learning outside the classroom. On this platform, students become teacher partners in the learning process in the fifth-grade class. The students accomplished the program activities at school for 108 working days or five months, starting from August to December 2022. One of the learning programs is to improve Literacy and numeracy learning at the basic education level. Methods of strengthening literacy learning are selecting particular reading texts for the elementary level, basic literacy concepts, good practice of literacy strategies, and the School Literacy Movement. The method of implementing reinforcement for numeracy is to provide good practice of numeracy strategies through games and media to improve students' numeracy. The learning outcomes were based on the result scoring test of the Minimum Class Competency Assessment students at the 5th grade elementary in the target school.